Role of Adjuvant Chemotherapy in Patients With Early Stage Uterine Papillary Serous Cancer. Issue 8 (1st November 2011) - Mahdavi, Ali; Tajalli, Tania R.; Dalmar, Ahmed; Vasilev, Steven A.; Lentz, Scott E.; Berman, Michael L.
Abstract : Objective: Uterine papillary serous carcinoma (UPSC) is an aggressive subtype of endometrial cancer. We studied survival outcomes in patients with stages I/II UPSC. Materials: A retrospective, multi-institutional study of patients with stages I/II UPSC was conducted. Patients underwent surgical staging followed by observation, adjuvant platinum-based chemotherapy (CT), or radiation therapy (RT). Continuous variables were compared via Wilcoxon rank sum test; Fisher exact test was used for the unordered categorical variables. Kaplan-Meier curves were used to estimate survival. Results: Thirty-nine women were diagnosed with stage I (n = 30) or II (n = 9) UPSC, with a median follow-up of 52 months. Of the 26 patients who did not receive adjuvant CT, 9 developed recurrences and 8 died of their disease. Of the 10 patients with no myometrial invasion who did not receive adjuvant CT, 3 developed recurrences and died. Of the 7 patients who underwent RT, 2 developed distant recurrences and died. Of the 13 patients who underwent CT, 1 developed vaginal recurrence. The 5-year overall (OS) and progression-free survival (PFS) rates for the adjuvant CT group were 100% and 92%, respectively, compared with 69% and 65% for those who did not receive CT ( P = 0.002 OS, P = 0.002 PFS). The 5-year OS and PFS rates for RT group were both 71%. Conclusions: Patients with stages I/II UPSC are at significant risk for distant recurrence and poor survival. Platinum-based adjuvant CT may decrease recurrence rate and improve survival in women with early and well-staged UPSC.